REGARDING THE DEVELOPMENT OF THE INFRASTRUCTURE OF THE AVIATION INDUSTRY IN THE ENERGY ASPECT - BOIKO , SERGEY; KOTOV, OLEKSII; KRYVYKH, YULIA; VYSHNEVSʹKYY, SVIATOSLAV; GVOZDIK, STANISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article defines that Ukraine is a transit country, which gives it opportunities for development and obliges to constantly develop the transport industry at the national level. To date, hostilities are taking place in Ukraine on part of its territories, and in the rest of the territory, the transport infrastructure is in a dilapidated state and needs modernization, and in some places, complete replacement. Meanwhile, vehicles, including aviation, are gradually switching to new alternative types of fuel, which in turn requires the development of the corresponding infrastructure. It should be noted that if we consider aviation transport, in addition to traditional types of fuel, which are currently consumed by the vast majority of aircraft, alternative types of fuel are gradually being introduced. Among them, hydrogen technologies and electric power technologies should be singled out. Therefore, the question of researching the development of the energy component of the air transport infrastructure, including in the aspect of the post-war reconstruction of Ukraine, is relevant. The article analyzes the peculiarities of the development of the energy infrastructure of aviation infrastructure during the post-war reconstruction of Ukraine. In order to increase the reliability of power supply to aviation facilities, the authors proposed the use of electric power generating units based on hydrogen technologies, which require relatively small storage volumes, have high maneuverability, are environmentally friendly and do not depend on the topography of the area, which allows them to find wide application, especially in interaction with sources of distributed generation with stochastic modes of operation.